2021
DOI: 10.1096/fj.202002049r
|View full text |Cite
|
Sign up to set email alerts
|

PHD3 mediates denervation skeletal muscle atrophy through Nf‐κB signal pathway

Abstract: Skeletal muscle is the largest organ of the body, the development of skeletal muscle is very important for the health of the animal body. Prolyl hydroxylases (PHDs) are the classical regulator of the hypoxia inducible factor (HIF) signal pathway, many researchers found that PHDs are involved in the muscle fiber type transformation, muscle regeneration, and myocyte differentiation. However, whether PHDs can impact the protein turnover of skeletal muscle is poorly understood. In this study, we constructed denerv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 94 publications
(190 reference statements)
0
3
0
Order By: Relevance
“…Our and other studies have shown that NF-κB signaling is involved in RA-, aging-, and denervation-related muscle atrophy in animal models (Li et al, 2020;Li et al, 2021b). To investigate if this signaling pathway in response to TNFα is associated with muscle atrophy and grip strength in human, we conducted a pathway-based genetic association study in population, and found that the weighted genetic risk score of NF-κB pathway in response to TNFα (including 198 genes) was significantly associated with grip strength, suggesting this TNFα-induced NF-κB pathway is related to muscle atrophy in human (Supplementary Table S3; Table 1).…”
Section: Nf-κb Signaling In Response To Tnfα Is Associated With Grip ...mentioning
confidence: 78%
“…Our and other studies have shown that NF-κB signaling is involved in RA-, aging-, and denervation-related muscle atrophy in animal models (Li et al, 2020;Li et al, 2021b). To investigate if this signaling pathway in response to TNFα is associated with muscle atrophy and grip strength in human, we conducted a pathway-based genetic association study in population, and found that the weighted genetic risk score of NF-κB pathway in response to TNFα (including 198 genes) was significantly associated with grip strength, suggesting this TNFα-induced NF-κB pathway is related to muscle atrophy in human (Supplementary Table S3; Table 1).…”
Section: Nf-κb Signaling In Response To Tnfα Is Associated With Grip ...mentioning
confidence: 78%
“…Jun N-terminus kinase (JNK) and STE20-like protein kinase activation induced by oxidative and genotoxic stress causes the nuclear translocation of FoxO independent of Akt regulation (Hay, 2011). It has been reported that DEN increased the JNK phosphorylation in mouse muscle (Li et al, 2021). These findings suggest that FoxOmediated ubiquitin-proteasome system-dependent proteolysis in concurrent loaded muscle is independent of Akt regulation.…”
Section: Discussionmentioning
confidence: 99%
“…To that end, the advent of CRISPR/Cas9 gene editing technology should enable more rapid generation of mice with muscle‐specific ablation of cytokines. For instance, the recently reported transgenic mice with Cas9 expression driven by human skeletal actin (HSA)‐Cre [177] and muscle creatine kinase (MCK)‐Cre [178] would offer a convenient way to knock out or knock down cytokine genes of interest in muscle by delivering specific sgRNAs. Muscle‐specific activation of cytokine gene expression would also be informative and potentially applicable in therapeutics, and the CRISPR activation technology (CRISPRa) provides a powerful tool [179].…”
Section: Concluding Remarks and Future Directionsmentioning
confidence: 99%